CRP, AN INFLAMMATORY BIOMARKER IN TYPE 2 DIABETES MELLITUS - Ali, Sobia; Khan, Mudassir Ahmad; Khan, Muhmmad Ali (Journal of Postgraduate Medical Institute, 2015)
Objective: To find out hs-CRP levels in type 2 diabetic patients with and withoutCHD and to further evaluate association of hs-CRP with glycosylated hemoglobinand lipid profile. Methodology: A cross- sectional / analytical study was conducted. Group Acomprised of 100 type 2 diabetic patients without CHD and Group B comprisedof 100 type 2 diabetic patients with CHD. All the patients were randomlyselected from Khyber teaching hospital (KTH) and Hyatabad MedicalComplex (HMC). Blood Glucose, Glycosylated Hemoglobin, Lipid profile andhs-CRP levels were assessed. Results: The mean hs-CRP, FBS and glycosylated hemoglobin values were significantly(P< 0.05) high in type 2 diabetic patients having CHD than type 2diabetic patients without CHD. Moreover, hs-CRP also showed a significant(P< 0.05) positive association with FBS and HbAlc and negative associationwith HDL-C (P< 0.05). Conclusion: It can be concluded from the study that raised levels of plasmahs-CRP in type 2 diabetic patients may contribute to ongoing atheroscleroticprocesses leading to the development of coronary heart disease in these patientsand this can be used as a marker of development of atherosclerosis inpatients with diabetes mellitus.